Peningkatan Penguasaan Kosa Kata Bahasa Inggris Melalui Metode Total Physical Response (TPR) pada Anak Usia Dini (PIAUD IAIN Kudus, 2016)
IMPROVING ENGLISH VOCABULARY MASTERY THROUGH TOTALPHYSICAL RESPONSE METHOD IN EARLY CHILDHOOD. In general, the languagecomponent consists of three, namely grammar, vocabulary, and pronunciation.Vocabulary is a language center and is important for language learning. Withoutsufficient vocab, one can not communicate effectively or express all his ideas eitherorally or in writing. Teaching vocabulary especially in early childhood should beemphasized, because having sufficient vocabulary will make it easier for childrento communicate. In addition, early childhood is a very vulnerable or golden age,because at this time the child’s brain has accelerated the development of up to 80%of the entire adult brain. Total Physical Response is the perfect method for learningEnglish for early childhood because the general purpose of the TPR method isto teach oral language skills at the beginner level. Thus, students understandspoken language before developing speaking skills, emphasizing the transfer ofcommunication information.